STEAM in environment and science education: Analysis and bibliometric mapping of the research literature (2013-2020). Issue 1 (February 2021) - Santi, Kurnia; Sholeh, Sofyan M.; Irwandani,; Alatas, Fathiah; Rahmayanti, Henita; Ichsan, Ilmi Zajuli; Mehadi Rahman, Md.
Abstract: The suitability of the science-arts convergence is currently being actively discussed because it is important in educating students to become more creative and knowledgeable people. This type of research is a quantitative study using a bibliometric approach. This study aimed to carry out systematic mapping of research trends in the STEAM field in science education. We analyzed 30 articles from 25 leading journals from 1 January 2013 to 31 August 2020 (8 years period), the metadata obtained from the Scopus database was then analyzed and mapped using VOSviewer software. The articles were written by 91 authors related to 64 in 13 countries. South Korea is emerging as the most productive country. 91% of authors in this publication have only 1 publication 8% have 2 publications and another 1% have 3 publications. The 5 clusters have been reviewed, the keywords that appear most often and become the most researched topics, namely STEAM education, STEAM, engineering education, education computing, and students. New and less researched variables in the STEAM field are presented along with future study opportunities to be discussed.